Rationalities in The Institutionalism: Ideas from Thorstein Veblen and Pierre Bourdieu - Eslava Gómez, Adolfo (Sociedad y Economía, 2012)
This article shows Thorstein Veblen´s contributions in economic sciences and puts them in dialogue with other social analysis perspectives. First of all, it presents the institutions in classical institutionalism view and then exposes relevant categories for understanding economic phenomena. Following, it presents Pierre Bourdieu´s economic sociology understood as a heterodox view about economic institutions. At the end it proposes interdisciplinary dialogue as a way to ensure the convergence of knowledge aimed at the social science building.